Tinjauan Penipuan dengan Motif Pemalsuan Barcode Qris Dari Aspek Penanggulangan Berdasarkan Hukum Pidana Indonesia - Rindy Baruadi; Moh. Rusdiyanto U. Puluhulawa; Vifi Swarianata (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research aims to determine criminal acts of fraud with the motive of counterfeiting Qris Barcodes in terms of the aspect of prevention through the Indonesian Criminal Law. This research is normative research which is analyzed descriptively, using a law and case approach. The results of the research are that regulations regarding criminal acts of fraud are generally regulated in Article 378 of the Criminal Code, and to strengthen the legal basis it can be accommodated through Article 35 of Law Number 19 of 2016 concerning Information and Electronic Transactions. As a special law, the ITE Law is at least a guideline and legal basis for members of the public in carrying out activities in the online world. Overcoming the occurrence of criminal acts of online fraud is carried out with preventive (non-penal) and repressive (penal) efforts. Repressive efforts in this case are regulated based on Article 35 of the ITE Law and Article 378 of the Criminal Code. Meanwhile, preventive efforts are carried out by taking precautions so that criminal acts of online fraud can be minimized without applying criminal law, but rather by carrying out preventive efforts before the criminal act occurs, such as improving the community's economy, socializing to the public how to use the internet properly and the characteristics of electronic transaction-based criminal acts of fraud.